Nonlinear static analysis of concrete bearing-wall type, low-rise single-family dwelling structures - Germar, Fernando J. (2011)
A new construction system being introduced in the housing industry is the concrete bearing-wall type construction. This construction system, without beams and columns, relies primarily on walls for bearing and lateral resistance. To assess the seismic capacity of this wall type, pushover analysis was performed employing 2-D lattice modeling technique using SAP2000. The 2-D lattice modeling technique was checked against experimental results of two squat-type wall specimens previously tested by other researchers and excellent was found. Displacement capacity had been predicted by 2-D lattice model in the two wall specimens with an accuracy of within ten percent of the test value. 2-D Lattice modeling was likewise used in the pushover analysis of a representative two-storey structure wall in the Philippines. Resulting failure pattern of nonlinear static analysis using 2-D lattice model also showed excellent agreement with ANSYS 3-D nonlinear time-history analysis result using solid modeling. Estimated displacement capacity though gave higher results compared to the 3-D analysis result. Comparing the couple of minutes computing time of nonlinear static analysis using 2-D lattice model with 10 hours of solution of nonlinear time-history analysis using solid model, 2-D lattice modeling proves to be a very practical modeling technique for nonlinear static analysis of walls. Moreover, results of analysis showed concrete bearing-wall system to be a viable construction system for the housing industry.
Thesis (Ph.D. Civil Engineering)--University of the Philippines, Diliman.
Keywords: Dwellings -- Design and construction; Concrete bearing walls